Accelerative oxygen evolution by Cu-doping into Fe-Co oxides. Issue 1 (20th November 2019) - Zhang, Qiaoqiao; Liu, Ning; Guan, Jingqi
Abstract : Low overpotentials of 256, 271, and 226 mV at 10 mA cm −2 can be achieved over FeCoCuO x supported on a GCE, a Pt electrode, and Ni foam, respectively, in an alkaline electrolyte. Abstract : Development of cost-efficient, high-performance and robust earth-abundant electrocatalysts for the oxygen evolution reaction (OER) is a continuous challenge. Herein, we develop a facile sol–gel strategy to fabricate a ternary Fe-Co-Cu oxide for efficient electrocatalysis of water oxidation. Low overpotentials of 256, 271, and 226 mV at 10 mA cm −2 can be achieved over FeCoCuO x supported on a GCE, a Pt electrode, and Ni foam, respectively, in an alkaline electrolyte. Due to the enhanced charge transfer ability and electrochemically active surface area, trimetallic FeCoCuO x is more active than binary FeCoO x and among the most active OER catalysts to date.